Seasonal dynamics of autotrophic respiration in boreal forest soil estimated by continuous chamber measurements - Pumpanen, Jukka; Kulmala, Liisa; Linden, Aki; Kolari, Pasi; Nikinmaa, Eero; Hari, Pertti (Finnish Environment Institute, 2016)
Peer reviewed